MANEJO DE LOS COSTOS E INGRESOS RELEVANTES EN EL ANÁLISIS ECONÓMICO: DECISIÓN DE ACEPTAR UNA ORDEN ESPECIAL - Porlles L., José A. (2006)
In the context of the continuous improvement of the companies, the engineer of processes is and he will see progressively immersed in projects and decisions that have an impact in the economic operations of the companies. The correct definition of the problem, exposition and the election between alternatives, to establish priorities and to seil its proposal to the management, he is subject to it's professional capacity to know how to analyze the nature and magnitude of the economic results in the central objective of the company. The intention of this series and next articles is to examine the concepts connected to a problematic individual and to offer the methodology of how justitying projects of improvements of utilities. In the present work, the handling of the costs and operative income begins with the tie decisions to accept a special order in processing planis.